Energy-1 ('NRG-1'): don't believe what the newspapers say about it being legal. Issue 12 (18th November 2011) - Wood, David M; Davies, Susannah; Cummins, Aaron; Button, Jennifer; Holt, David W; Ramsey, John; Dargan, Paul I
Abstract : A 31-year-old man purchased the legal high Energy-1 (NRG-1) over the internet; this was advertised as containing the compound naphthylpyrovalerone (NPV), which at the time was currently legally available in the UK. He ingested 1 g of this substance and developed a prolonged high associated with palpitations, sweating and insomnia. Analysis of both the powder and serum samples from the patient demonstrated that he ingested two classified recreational drugs β-keto- N -methylbenzodioxolylpropylamine (butylone) and methylenedioxypyrovalerone (MDPV) rather than the legal substance NPV. Users of legal highs need to be aware that legal highs purchased over the internet may contain illegal substances and therefore they may be liable for prosecution if found in possession of these substances. Future educational campaigns aimed at recreational drug and legal high users should include reference to the potential legal implications of buying these substances.